Exploring the Impact of Father’s Demise among Female Adolescents - Rabia Farooqi; Ayesha Khan (NUST Journal of Social Sciences and Humanities)
The present study is intended to explore the impact brought about by parental demise among female adolescents. Moreover, examining the societal role, particularly the part played by the family system, after the death of a father and its effect on an adolescent’s life perception. Data was collected through in-depth interviews from 4 adolescents aged between 17-19 years, accumulated by a purposive sampling method and analyzed through interpretative phenomenological analysis. Findings demonstrated that adolescents who encountered the loss of their fathers face numerous problems impacting their emotional, cognitive, and behavioural well-being. The absence of parents brings a drastic change in an entire life affecting their mental health leading to low self-esteem, depression, anxiety as well as emotional sufferings. The major issues highlighted during the study were life disruption, financial crisis, lack of support in terms of both financial and emotional aspects from extended family. Moreover, the family system played a detrimental role in the adversities encountered. Furthermore, participants stressed that children having both parents attained support, attention, emotional bonding, and encountered fewer social, psychological, and emotional issues. They constantly grieved the parental loss and faced a lack of care, that significantly affected their well-being. These findings help in understanding the problems associated with lack of parental bonding in connection with father’s loss, whereas its long-lasting impact spread throughout one's life.